Performance Of Thermal Electric Cooling (TEC) Air Condition For A Small Office Space - Shamsudin, Shamsul Anuar; Abd Aziz, Muhammad Syahril; Sudin, Mohd Nizam; Ismail, Mohd. Farid; Huthaifa Ahmad Al-Issa (Penerbit UniMAP, 2021)
An experimental investigation on the TEC (thermoelectric cooler) air-conditioner with evaporative cooler that acts as condensing unit in a small of ice space was performed. Various engineering performance criteria of the system such as the Coef icient of Performance (COP) of the TEC plate, the COP of the developed product, the COP of evaporative cooler and the sound level of the product were evaluated. The tested area of ice size was 12 ft × 11 ft, used for light activities and with few equipment generating heat. As a result, the TEC air conditioner by evaporative cooling was developed that consists of several parts that include thermoelectric modules model TEC-12706, heatsinkfan, water heatsink, water pump, water pipeline, radiator, and evaporative cooler. This experiment found that the COP of the TEC plates condensed by evaporative cooling is 0.39. The optimum running current for the system is 5 A when the system’s COP achieved the highest values which is 1.7. The COP of the evaporative cooling decreases with the increment of the current supply to the TEC. Consequently, the 62.9 dB sound level of the system is acceptable.